If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x-9=7x-43
We move all terms to the left:
9x-9-(7x-43)=0
We get rid of parentheses
9x-7x+43-9=0
We add all the numbers together, and all the variables
2x+34=0
We move all terms containing x to the left, all other terms to the right
2x=-34
x=-34/2
x=-17
| 5x-1/2=-7/2x-7/3 | | 5+3x-x^2=0 | | 7x-5.31=-0.20 | | 5x+11‐3x=-x+62 | | -x-29=13+2× | | -6w+3(w+6)=6 | | 4(11-x)+3x=-2x-2 | | n+6=6-n | | 1/2n+28=30 | | 10x=258 | | 6+2(x+7)=-11(12+x)-6x | | -1/2(b+2)=-1-3b | | 8y+4+2y+6=90 | | y5–6=8 | | 2(3-x)+6=4x | | y/5–6=8 | | 3x-5.95=-3.49 | | -11+7a=6a-4 | | −6r+8−7r=−5 | | 6(2-8r)+4=100+108 | | 1/2(t+7)=32 | | 5/t(t+7)=2/7t+23 | | 2x+8=6x-26 | | 2(2x+3)-15x=2x-7 | | (t+7)=32 | | 5x-5.52=-4.32 | | m=4m+9 | | 0.5/x=20 | | -5(3x-7)+11=x | | 6w=45-4w | | 2^x+7=5/4 | | 3/2x-5=2/x-4 |